FAKTOR PROGNOSTIK YANG MEMPENGARUHI TERJADINYA INKONTINENSIA PASCABEDAH PADA PASIEN HIRSCHSPRUNG DI RSUP DR. SARDJITO TAHUN 2008-2012 - , Arif Kurniawan, Dr. dr. Rochadi, SpB, SpBA (K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Introduction: Hirschsprung disease is a common disorder causing obstruction and enterocolitis in children with incidence of 1:5.000 live births. Various studies have been conducted previously associated complications of constipation after surgery. Procedures such as engineering endorectal Soave pull-through is one of the surgical techniques used in the definitive treatment of Hirschsprung disease. Objective: The aim of this study were: to determine the magnitude of the incidence and factors affecting incontinence postoperatively in patients with Hirschsprung disease Soave procedure. Patients with megacolon (Hirschsprung's disease) who performed the operation Soave endorectalpull through at the Children's Surgical Hospital. Dr. Sardjito Yogyakarta during the period January 2008 to February 2012. Material and methods: This study is an observational analytic study with retrospective cohort study design, which is one form of observational studies (nonexperimental). Statistical test used was chi-squre test with an alternative test, t-test and logistic regression with p <0.05 were considered significant. Kaplan Meier survival analysis to get a free picture of the number of incontinence. Results: Five patients had postoperative fecal incontinence, 2 which is located in Yogya and 3 outside Yogya, but this is not a statistically significant difference (p = 1) (RR = 1158, 95% CI: 0.212-6.325). All patients who had fecal incontinence were men but not statistically significant (p = 0.573). Weight loss does not significantly influence the occurrence of postoperative fecal incontinence (p = 0.315) (RR = 3.84, 95% CI: 0.46 - 31.95). Age time of surgery did not give significant differences on the incidence of postoperative fecal incontinence (p = 0.327) (RR = 2.833, 95% CI: 0.520-15.440). Meconium evacuation was also not significant to the occurrence of fecal incontinence (p = 0.169) (RR = 0.214, 95% CI:0.026-1.790). No significant effect on the operating time of the occurrence of postoperative fecal incontinence (p = 0.473) (RR = 0.522, 95% CI:0.069-3.931). Location aganglion also not significant overall incidence of faecal incontinence (p = 0.363). Old patient was also not statistically significant (p = 0.610). Preoperative hemoglobin values did not affect the incidence of fecal incontinence were significantly (p = 0.99) (RR = 4083, 95% CI:0.10-9.30). Preoperative albumin does not make a difference which was statistically significant (p = 6.44) (RR = 1.891, 95% CI0.344-10.389). Age at surgery <6 months free number incontinence lower than age>12 months with log rank0.249, (p = 0.883). Evacuation meconium>24 hours incontinence free number is higher than the <24 hours with log rank2.772, (p = 0.096). Operating time <120 minutes free incontinence numbers lower than the>120 minutes with log rank0.135, (p = 0713). Length of <12 days incontinence free number is lower than the length of>12 days with log rank0.959, (p = 0.619). Preoperative hemoglobin <14 points higher than non incontinence preoperative hemoglobin>14 with log rank 0.986 (p = 0.029). Preoperative albumin <3.5 points lower than non incontinence preoperative albumin â¥3.5 with log rank 0.321, (p = 0.571). Body weight <10 kg free number incontinence lower than the>20 kg with log rank2.466, (p = 0.291). Conclusion: Based on the results of the study can be drawn a conclusion that all predictor variables did not differ significantly on the incidence of urinary incontinence.